A SELECTIVE UPREGULATION OF GABAA RECEPTOR SUBUNIT EXPRESSION IS ASSOCIATED WITH THE HYPOTENSIVE EFFECTS OF GANAXOLONE IN MALE HYPERTENSIVE SCHLAGER MICE. (April 2021) - Gueguen, Cindy; Le-Pham, Phuong-Nhan; Jackson, Kristy L; Paterson, Madeleine R; Esler, Murray; Marques, Francine Z; Lambert, Elisabeth; Head, Geoffrey A
Abstract : Objective: Ganaxolone is a synthetic form of allopregnanolone, an allosteric modulator of gamma aminobutyric acid type A receptors (GABAAR). Allopregnanolone reduced blood pressure (BP) in male BPH/2J mice with neurogenic hypertension (Stevenson et al., 2017), which suggests that a lack of tonic inhibition in the forebrain mediates the hypertension. The hypotensive effect of allopregnanolone was associated with an upregulation of the GABAAR alpha4 and delta-subunit mRNA in the hypothalamus and medial amygdala of BPH/2J mice. The objective of this study was to investigate the temporal association of the antihypertensive effects of ganaxolone and the alteration in the different GABAAR subunits in the forebrain of BPH/2J mice. Design and method: 12-week-old hypertensive BPH/2J and normotensive BPN/3J male mice were implanted with a telemetry probe to record BP and heart rate. Cardiovascular responses to stress tests and pentolinium were measured before and after administering vehicle or ganaxolone (5 mg/kg/day, subcutaneous minipumps) for 2 weeks. The mRNA expression of the GABAAR subunits was measured by real-time PCR 1 to 2 weeks after the beginning of the treatment in vehicle or ganaxolone-treated BPH/2J mice. Results: After 2 weeks, ganaxolone reduced BP by 10.7 mmHg (P < 0.001) in male BPH/2J mice and reduced the pressor responses during restraint (-8.2 mmHg, P < 0.001) and dirty-cage switch (-12.4 mmHg, P < 0.001) stresses compared with pre-treatment. One-week treatment with ganaxolone or vehicle had no effect on cardiovascular parameters on either strain. Ganaxolone-treated BPH/2J mice had increased mRNA expression of alpha4-subunit and showed a trend towards increased delta-subunit of hypothalamic GABAAR compared to vehicle-treated BPH/2J. None of these effects were seen at 1-week post-treatment and in BPN/3J mice. Conclusions: Ganaxolone reduced hypertension and the cardiovascular response to stress in male BPH/2J mice but only when upregulated alpha4 and delta-subunit mRNA expression of the GABAAR was observed. Therefore, it is likely that the main mechanism of the delayed antihypertensive effects of ganaxolone in neurogenic hypertensive mice is dependent on upregulation of specific GABAAR subunits.